Erratum to: Holographic scalar and vector exchange in OTOCs and pole-skipping phenomena - Kyung-Sun Lee; Mitsuhiro Nishida; Keun-Young Kim (Journal of High Energy Physics, 2021)
The original article has been corrected. Because of an error in the production stage, in the original paper the order of the authors was wrong. The correct order for the authors is: Kyung-Sun Lee, Mitsuhiro Nishida and Keun-Young Kim. The originally published wrong file has been replaced online.